Lectin receptors as markers of lymphoid cells. II. Reed-Sternberg cells share lectin-binding properties of monocyte macrophages. - Strauchen, J. A. (1984)
The origin of the Reed-Sternberg cells of Hodgkin's disease is controversial with proponents of transformed lymphocyte and macrophage histiocyte derivations. Lectin receptors are potentially useful new cell markers in the investigation of lymphoproliferative disease. In this study, the lectin-binding properties of the Reed-Sternberg cell were investigated in an effort to clarify the cell of origin. Utilizing a simple peroxidase technique applicable to formalin-fixed, paraffin-embedded tissue, lectin binding was studied in 13 cases of Hodgkin's disease. Reed-Sternberg cells were found to bind cytoplasmic concanavalin A, but not Arachis hypogaea (peanut agglutinin) or Lotus tetragonolobus (asparagus pea). These are the lectin-binding properties of macrophage histiocytes rather than transformed lymphocytes. Lectin-binding studies support the macrophage origin of the neoplastic cells of Hodgkin's disease.